Perceived benefits of adventure recreational participation - Che Ibrahim, Nur Syuhada; Mohammad Afandi, Syamsul Herman; Samdin, Zaiton (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
Malaysia is experiencing increasing participation in adventure recreational activities which include Mountain Biking, Wall Climbing, Bicycle Motor Cross and skateboarding. Although adventure recreational activities have always been associated with risk taking and danger, but there are valuable outcomes from partaking of such activities towards personal health and wellbeing. The objective of this study was to assess the valuable contribution of adventure activities to personal health and wellbeing of an individual who participate in this kind of activity. On-site survey was conducted at Putrajaya Challenge Park and a total of 198 usable questionnaires were obtained. In terms of perceived benefit, the mean score of Education benefit showed the highest score (3.2576) compared to the other perceived benefits which were the Psychological (3.1439), Physical (3.1128) and Social benefit (2.7963). The study provides useful information for any related parties to planning and managing recreational area especially like adventure sports.